A linear-to-rotary hybrid nanogenerator for high-performance wearable biomechanical energy harvesting. (January 2020) - Yan, Cheng; Gao, Yuyu; Zhao, Shenlong; Zhang, Songlin; Zhou, Yihao; Deng, Weili; Li, Ziwei; Jiang, Gang; Jin, Long; Tian, Guo; Yang, Tao; Chu, Xiang; et al.
Abstract: Harvesting biomechanical energy from low-frequency human body motions is a challenging but promising approach to powering the future wearables. Herein, we report a linear-to-rotary hybrid nanogenerator (LRH-NG) to effectively harvest low-frequency body biomechanical energy via a frequency enhancement strategy. Remarkably, the generated current and voltage by the LRH-NG from human body movement are respectively enhanced up to 3.1 times and 3.6 times of that at the basic frequency (2 Hz). Furthermore, the LRH-NG was demonstrated as an on-body electricity generator that can sustainably power a body area network with a temperature sensor and a humidity sensor for personalized health care. The designed LRH-NG may open up a new approach for high-performance low-frequency wearable biomechanical energy harvesting as a sustainable and pervasive energy solution in the era of the Internet of things. Graphical abstract: Image 1 Highlights: Harvesting low-frequency biomechanical energy is challenging but promising approach to powering the future wearables. The linear-to-rotary hybrid nanogenerator (LRH-NG) can effectively convert the low-frequency biomechanical linear motions into high-frequency rotary motions. The generated current and voltage by the LRH-NG from human body movement were enhanced up to 3.1 and 3.6 times of that at the basic frequency (2 Hz), respectively. The energy generated from human walking by the LRH-NG with an enhancement factor of Gf1 could power a body area network for personalized health care. The designed LRH-NG opens up a new approach for high-performance on-body biomechanical energy harvesting as renewable and sustainable power sources for wearable electronics.